The audit approach to the internal control in electronic data processing (EDP) environment / Rahimah Ibrahim - Ibrahim, Rahimah (Faculty of Accountancy, 1990)
Electronic Data Processing (EDP) system is one of the most important technological developments of the twentieth century. The use of EDP in profit-oriented companies began in the early 1950s. Little attention has been given to the use of accounting information system.